IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING NEWS ITEM TEXT THROUGH COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TECHNIQUE - Paramita; Rahmah (Universitas Negeri Medan, 2013)
This study focuses on improving students’ achievement in writing News Item text through Cooperative Integrated Reading and Composition (CIRC) Technique. This study was conducted by using classroom action research. The subject of this research was the grade X students of SMA Mitra Inalum. Twenty four students were taken as the sample. The research was conducted in two cycles. First cycle was conducted in four meetings. The second cycle was conducted in two meetings. The instruments for collecting data were quantitative data (writing test) and qualitative data (observation sheet, diary note, and questionnaire sheet). Based on the data analysis, students’ score kept improving in every test. The mean of the students’ score in the first competence test was 38.4, in the second competence test was 75.4 and in the third competence test was 81.9. The result showed that Cooperative Integrated and Reading Composition (CIRC) technique improved students’ achievement in writing news item text.